TAHAPAN COMMUNITY RELATIONS DALAM KEGIATAN CSR KONSERVASI LINGKUNGAN (Studi Kasus Terhadap Kegiatan CSR PT Djarum Pada Konservasi Lereng Gunung Muria) - Mufid Salim (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
A company is required not only provide jobs and pay taxes, but also must be able to be a good neighbor with a reciprocal relationship with the community, as well as play a role in improving the welfare of the community through various community development programs. Relationship between the company and the community then opened the activity of corporate social responsibility. Sustainability of the company relationship can be influenced by how the company manages its social responsibility to the communities where it operates and build a good communication to them. So that, the community relations activities are part of the public relations activities. This research which entitled “Community Relations Stage in CSR activity of Environmental Conservation” (Descriptive Qualitative Study of CSR Activity of PT Djarum in environment conservation on MountMuria, Kudus) discuss about the Defining the Problem Stage, Planning and Programming Stage, Taking Action and Communication Stage, and Evaluating The Program Stage of Konservasi Lereng Muria activity. This research also discuss how the PT Djarum efforts in building relationships and communication with the Kudus society, students, and local community that living in the area of Mount Muria, Kudus, Central Java. Konservasi Lereng Muria is PT Djarum’s activity in Corporate Social Responsibility that directed to answer the problem of local community based on environment damage in Mount Muria. In this environment conservation program, PT Djarum involving students and the local community of Mount Muria to plant productive tree in some critical areas in Mount Muria, Kudus, Central Java.